Study on pickling technology to control fouling of ceramic membrane treating secondary treated effluent. (16th September 2022) - Wang, Fengchao; Zhang, Shoubin; Jiao, Wenhai; Chen, Jingying; Zhao, Shikai; Ma, Guoqiang; Liu, Guicai
Abstract: The application of membrane technology in the field of water treatment was increasingly widespread, but membrane fouling still restricted its development, and the membrane needed to be chemically cleaned. This research focused on the high-efficiency pickling technology of ceramic membrane, and developed the cleaning technology of ceramic membrane in cooperation with surfactant. In the experiment, the municipal secondary effluent was used as the raw water, and the single-step, mixed and step-by-step cleaning effects of three strong acids, three weak acids and surfactants on ceramic membranes and polyvinylidene difluoride (PVDF) membranes were investigated. For ceramic membrane, the optimal cleaning combination was H2 SO4 first and then DTAC, and the flux recovery rate could reach 96.94%; for PVDF membrane, the optimal cleaning combination was HNO3 first and then H2 SO4, and the flux recovery rate could reach 93.72%. In addition, the surface of initial, polluted, and cleaned membranes were analyzed by scanning electron microscope and contact angle, and the fouling mechanism of the ceramic membrane was analyzed. The results showed that through physical cleaning and chemical cleaning, most of the pollutants on the membrane surface and pores were removed. The cleaning method can effectively control the membrane pollution. HIGHLIGHTS: The effects of different cleaning agents on ceramic membrane and PVDF membrane were compared. The running time of ceramic membrane is longer after optimal single acid cleaning. The flux recovery rate of both membranes can reach more than 90% after optimal cleaning. Combining microscopic characterization to determine the cleaning efficacy. Graphical Abstract